Strengthening SDIT Students Computational Thinking through Computational Thinking Activities - Unplugged Binary Digits and Product Codes - Susilo, Andi; Setiyaningsih, Timor; Novianti, Eva; Yahya (JEPTIRA, 2025)
Computational thinking (CT) is a key 21st-century competency that needs to be developed from elementary school level because it is related to problem-solving skills, logical thinking, and creativity in the context of digital technology. Teachers play a central role in integrating CT into learning, but many elementary school teachers are unfamiliar with the concept of CT or its learning strategies. One effective approach that is appropriate for the characteristics of elementary school students is the CT-Unplugged activity, a computer-free activity that represents core computer science concepts in a concrete and enjoyable way. This community service activity aims to improve the understanding and skills of SDIT Mafatih teachers in implementing two CT-Unplugged modules: how binary digits work and checking product code digits (check digits), as a means of strengthening students' CT. The training was conducted at SDIT Mafatih involving 23 teachers through material presentations, demonstrations, activity simulations, and lesson plan design. Evaluation used pre- and post-tests of CT knowledge as well as questionnaires on perceptions and confidence in teaching CT. The results showed an increase in teachers' knowledge scores regarding CT concepts and binary digit/product code materials, as well as increased confidence in adapting CT-Unplugged activities into classroom learning. Teachers also produced several learning activity designs that integrated the module with elementary school lesson themes. This activity demonstrated that structured CT-Unplugged-based training is effective in building CT literacy and pedagogical capacity in elementary school teachers.